Climate Sensitive Design Approach To Reduce the Urban Heat Island Effect: Case of Poligon Stream and Its Surroundings, İzmir - Saygın, Nicel; Tunçbilek, Leyla Nur (My University, 2023)
Climate change, destruction of the natural environment, high-rise buildings, intense urbanization, and high energy consumption are increasingly making urban living challenging. Climate change triggers this situation, creating an increased urban heat island effect. Outdoor thermal comfort is crucial for pedestrian health in urban areas. The growing heat island effect due to climate change leads to thermal comfort issues in cities, negatively affecting urban life. Different urban forms within cities provide different microclimatic comfort zones for pedestrians. We must adapt urban planning to climate conditions from macro to micro scales with a holistic perspective. This study examines how the heat island effect in the Poligon Stream, and its surrounding area can be reduced using a climate-sensitive design approach. The main purpose of this study is to enhance the urban microclimate around the Poligon Stream by proposing design solutions at various scales to mitigate the urban heat island effect. To calculate land surface temperature and the heat island effect, satellite data from the hottest day of the year 2022 was utilized. Wind and thermal comfort models were developed using meteorological data such as air temperature, global radiation, wind speed, and relative humidity. The morphological structure of the study area, along with the analysis results of meteorological parameters and land surface temperature, indicates that the cooling capacity in the district is considerably low. Due to the heat island effect, urban life reaches levels that adversely affect living conditions in the summer months. Resulting in substantial, sustainable urban design proposals, focusing on ecological, nature-based, and climate-sensitive approach, were developed, resulting in a 13% reduction in the urban heat island effect.

İklim değişikliği, doğal çevrenin tahribi, yüksek binalar ve yoğun kentleşme, yüksek enerji tüketimi gibi faktörlerden kaynaklanan bir sorun olarak giderek şehir içerisinde yaşamayı zorlaştırmaktadır. Bu durum, kentsel ısı adası etkisi oluşturarak iklim değişikliği tarafından tetiklenmektedir. Kentlerde açık hava termal konforu, kentsel alanlarda yaya sağlığı için önemlidir. İklim değişikliği nedeniyle artan kentsel ısı adası etkisi, kentlerde termal konfor sorunlarına yol açarak şehir hayatını olumsuz etkilemektedir. Şehirler içinde farklı kentsel formlar, yaya için farklı mikroklimatik konfor bölgeleri sunar. Şehir planlaması, iklim koşullarına makrodan mikro ölçeklere kadar bütünsel bir bakış açısıyla uyarlanmalıdır. Bu çalışma, Poligon Deresi ve yakın çevresindeki alanda iklime duyarlı tasarım yaklaşımı kullanılarak ısı adası etkisinin nasıl azaltılabileceğini incelemektedir. Bu çalışmanın temel amacı, Poligon deresi ve çevresindeki kentsel mikro iklimleri iyileştirmek, farklı ölçeklerde analizler oluşturularak iklime duyarlı kentsel tasarım önerisi sunmak ve kentsel ısı adası etkisini azaltmaktır. 2022 yılının en sıcak gününe ait uydu verisi üzerinden yer yüzey sıcaklığı ve ısı adası etkisi hesaplanmıştır. Hava sıcaklığı, küresel radyasyon, rüzgâr hızı ve bağıl nem verileri gibi meteorolojik veriler kullanılarak rüzgâr ve termal konfor modeli oluşturulmuştur. Çalışma alanının morfolojik yapısı, meteorolojik parametreler ve yer yüzey sıcaklığı analizi, ısı adası etkisi, termal konfor analizi ve rüzgâr analizi sonuçları, bölgenin soğutma kapasitesinin çok düşük olduğunu ve ısı adası etkisinin yaz aylarında şehir hayatını olumsuz etkileyecek düzeylere ulaştığını göstermektedir. Sürdürülebilir, ekolojik, doğa temelli ve mikro-iklim duyarlı kentsel tasarım önerileri geliştirilmiştir. Bu öneriler sonucunda ısı adası etkisi %13 oranında azaltılmıştır.
Kentsel ısı adası etkisini azaltmak için iklim duyarlı tasarım yaklaşımı: Poligon deresi ve çevresi, İzmir örneği
Keywords: Urban climatology; Urban heat island